Child and adolescent longitudinal growth data evaluation using logistic curve fitting with the use of the dynamic phenotype method - Novák, Ludvík; Kukla, Lubomír; Čuta, Martin (Scripta medica Facultatis medicae Universitatis Brunensis Masarykianae, 2008)
Body length and body weight are two forms of the organism's genotype expression. The growth curve of body length in newborns, the growth curve of body height in children and adolescents, and the growth curve of body weight from birth to adolescence express the individual dynamics of the body length and body weight phenotype development. The body length growth curve from birth to maturity is, according to Karlberg, divided into three components: Infancy (I), Childhood (C), and Puberty (P). This paper shows that not only the body length growth curve expressed in length size parameters (D) but also the body weight growth (G) of individual boys corresponds to a growth curve composed of the three I-, C-, P- components expressed by the construction of three separate logistic curves. Each individual logistic curve component distinctly fits, within the defined probability, into the set of the measured phenotype values of body length (D) or body weight (G). Each of the fitted logistic curves is determined by the three constants referred to as the parameters of the Dynamic Phenotype. In the body length growth trait the parameters of the Dynamic Phenotype are (D0, DLi, dDmax) and in the body weight growth trait the parameters of the Dynamic Phenotype are (G0, GLi, dGmax) for each I-, C-, P- logistic curve component. It is shown that the Dynamic Phenotype parameter method described not only determines logistic curve components, but also enables exact construction of the whole individual I-, C-, P- growth curve composed of the corresponding I-, C-, P- sections of the logistic curves. Each I-, C-, P- logistic growth curve component begins by age (t0) and the initial value of the variable (X0) of the I-, C-, P- logistic curve component. The inflexion point of the growth curve component marked by age (t*(X)) indicates the age of the maximal growth velocity of the variables (dXmax). The Dynamic Phenotype method can also be applied to the growth data represented by the average values estimated in the reference groups of probands and to the interpretation of the percentile growth curves.
Keywords: logistické modely; Longitudinal Studies; Humans; biometrie; dítě; Child; tělesná výška; růst; financování organizované; Phenotype; Financing, Organized; lidé; Growth; Biometry; vývoj dítěte; longitudinální studie; Child Development; Body Height; fenotyp; Adolescent; Statistics as Topic; Body Weight; tělesná hmotnost; statistika jako téma; Logistic Models; mladiství